2020
DOI: 10.1101/2020.03.26.009423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ergothioneine, a metabolite of the gut bacteriumLactobacillus reuteri, protects against stress-induced sleep disturbances

Abstract: The relationships between depression and gut microbiota, particularly those involving the immune system, have become a major focus of recent research. Here, we analyzed changes in gut microbiota and their sulfur metabolites in the feces of a depression rat model using the modified 14-day social defeat stress (SDS) paradigm. Our results showed that SDS increased fecal Lactobacillus reuteri in correlation with ergothioneine levels at around day 11, which continued for at least one month following SDS administrat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 66 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Matsuda et al [20] also reported that oral administration of ERGO prevented depressive behavior and depression-like sleep abnormalities in rats (Table 2). In their studies, preventive administration of ERGO (0.25 mgÁmL À1 ) via drinking water corresponding to ~30 mgÁkg À1 Áday À1 based on water intake and body weight, ameliorated social defeat stress (SDS)-induced social avoidance behaviors against other rats and sleep abnormalities such as an increase in rapid eye movement sleep [20]. Furthermore, they demonstrated that SDS substantially increases the levels of the fecal gut bacterium Lactobacillus reuteri in correlation with fecal ERGO level, implying a protective system against psychosocial stress in the microbiota-gut-brain axis [20].…”
Section: Depression and Stress-induced Sleep Disturbancementioning
confidence: 89%
See 3 more Smart Citations
“…Matsuda et al [20] also reported that oral administration of ERGO prevented depressive behavior and depression-like sleep abnormalities in rats (Table 2). In their studies, preventive administration of ERGO (0.25 mgÁmL À1 ) via drinking water corresponding to ~30 mgÁkg À1 Áday À1 based on water intake and body weight, ameliorated social defeat stress (SDS)-induced social avoidance behaviors against other rats and sleep abnormalities such as an increase in rapid eye movement sleep [20]. Furthermore, they demonstrated that SDS substantially increases the levels of the fecal gut bacterium Lactobacillus reuteri in correlation with fecal ERGO level, implying a protective system against psychosocial stress in the microbiota-gut-brain axis [20].…”
Section: Depression and Stress-induced Sleep Disturbancementioning
confidence: 89%
“…In fact, oral ingestion of ERGO (120 mg/100 g diet) for 2 weeks in mice significantly decreased the immobility time, an index of depression-like behavior, in forced swimming and tail suspension tests with a concomitant increase in ERGO concentration in the brain (~20 µgÁg À1 tissue, Table 2) [19], and the ingestion promotes neurogenesis in the hippocampus, indicating that oral ERGO ingestion exerts antidepressant-like activity, possibly via promotion of neurogenesis in mice [19]. Matsuda et al [20] also reported that oral administration of ERGO prevented depressive behavior and depression-like sleep abnormalities in rats (Table 2). In their studies, preventive administration of ERGO (0.25 mgÁmL À1 ) via drinking water corresponding to ~30 mgÁkg À1 Áday À1 based on water intake and body weight, ameliorated social defeat stress (SDS)-induced social avoidance behaviors against other rats and sleep abnormalities such as an increase in rapid eye movement sleep [20].…”
Section: Depression and Stress-induced Sleep Disturbancementioning
confidence: 95%
See 2 more Smart Citations